Spatio-temporal dynamics of vegetable crop production in India - Kundu, Suman Kumar (International Multidisciplinary Research Journal, 2012)
<!--[if gte mso 9]> Normal 0 false false false EN-IN X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif]--> Horticulture is a profitable and diversified option for the development of rural economy. Being endowed with its wide variable climate and soil, India has immense potentialities for the development of horticulture especially vegetable crops production. In the year 2009-10, India is the second largest producer of vegetables in the world (next to China). The present paper highlights the spatio-temporal variations in vegetable production in India by using the secondary data procured from various government websites and offices. The study reveals that in spite of phenomenal growth in vegetable crop production there is lack of any effective policy measures for wiping out the problems relating to low crop productivity, limited irrigational facilities and inadequate infrastructural set up. The existing policies failed to pave the way for sustainable horticulture practice in India.